Growth Response of Seedlings of Four Robusta Coffee (Coffea canephora Pierre. Ex. A. Froehner) Clones to Drought Stress - Novie Pranata Erdiansyah; Ade Wachjar; Eko Sulistyono; Supijatno Supijatno (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Drought is one of the limiting factors for the growth and yield of coffee plants. Drought due to long dry season has caused many losses for coffee plantations. This study aimed to evaluate the response of four Robusta coffee clones to drought stress at seedling stage and determine the best clone with high tolerance to drought. The study was conducted in Indonesian Coffee and Cocoa Reseach Institute (ICCRI) Jember, East Java in November 2018–Mei 2019. The experimental design used a Randomized Block Design (RCBD) with two factors. The first factor has consisted of five levels drought through providing volume watering based coefficient and evaporation value of free water surface (Eo), namely: 0.5 Eo; 1.0 Eo; 1.5 Eo; 2.0 Eo; 2.5 Eo (control). The second factor has consisted of four Robusta coffee clones, namely: BP 409 (drought tolerant clone); BP 308; BP 939 and BP 358 (vulnerable to drought stres). The result showed that reduction in the volume of watering from 2.5 Eo until 0.5 Eo causes drought, reduce coffee growth linearly. Clone BP 409 and BP 939 had better tolerance of drought stress compared with BP 308 and BP 358. The anatomical adaptation of leaves of BP 409 to drought stress was by thickening of wax layer and palisade tissue. BP 939 thickened its leaves due to drought stress as a mechanism of adaptation to such condition.